Radial velocity and light curves analysis of the eclipsing binary NN Vir - Pazhouhesh, R.; Melendo, E. G. (Одеські астрономічні публікації, 2017)
The eclipsing binary NN Vir is a short period system showing an EW-type light curve. Photometric Observations of NN Vir were done by Gomez-Ferrellad & Garcia-Melendo (1997) at Esteve Duran Observatory. We used photometric Data of NN Vir for light curve analysis. The available spectroscopic data of NN Vir is new and we also used the first radial velocity Data of this system obtained by Rusinski & Lu (1999) for analysis. The radial velocity and light curves analysis was made with the Latest version of Wilson program (1998) and the geometric and physical elements of the system are derived. By searching the simultaneous solutions of the system, we have determined the masses and radii of the components : 1.89(Msun) and 1.655(Rsun) for the primary component; O.93(Msun) and 1.230(Rsun) for the secondary component. We estimated effective temperatures of 7030(K) for the primary and 6977(K) for the secondary component.